2009
DOI: 10.1084/jem.20090847
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 regulates the development, maintenance, and function of induced regulatory T cells

Abstract: Both the programmed death (PD) 1–PD-ligand (PD-L) pathway and regulatory T (T reg) cells are instrumental to the maintenance of peripheral tolerance. We demonstrate that PD-L1 has a pivotal role in regulating induced T reg (iT reg) cell development and sustaining iT reg cell function. PD-L1−/− antigen-presenting cells minimally convert naive CD4 T cells to iT reg cells, showing the essential role of PD-L1 for iT reg cell induction. PD-L1–coated beads induce iT reg cells in vitro, indicating that PD-L1 itself r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

56
1,535
11
30

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,787 publications
(1,632 citation statements)
references
References 75 publications
56
1,535
11
30
Order By: Relevance
“…51 PD-1 is also highly expressed on T regulatory cells and can promote their proliferation, further downregulating the immune response. 52 We provide evidence that in addition to proteinligand interactions as a mechanism of immune escape, immunomodulatory metabolic pathways are upregulated in medullary carcinoma. IDO-1 is an intracellular enzyme that degrades tryptophan (Trp) to kynurenine.…”
Section: Discussionmentioning
confidence: 85%
“…51 PD-1 is also highly expressed on T regulatory cells and can promote their proliferation, further downregulating the immune response. 52 We provide evidence that in addition to proteinligand interactions as a mechanism of immune escape, immunomodulatory metabolic pathways are upregulated in medullary carcinoma. IDO-1 is an intracellular enzyme that degrades tryptophan (Trp) to kynurenine.…”
Section: Discussionmentioning
confidence: 85%
“…Hence, viral factor(s) may increase CD4 + CD25 high Foxp3 + T cell numbers in BLV‐infected cattle, although BLV infects B cells whereas HIV and HTLV‐I infect T cells. In a previous study, PD‐L1 was associated with stable expression of Foxp3 in CD4 + CD25 + Foxp3 + T cells, and enhanced Treg function 47. Moreover, PD‐L1 promoted the development of CD4 + CD25 + Foxp3 + T cells from naïve CD4 + T cells in the presence of TGF‐β 47.…”
Section: Discussionmentioning
confidence: 93%
“…26,29 Since PM21-NK cells produce IFNγ in response to SKOV-3 cells, PM21-NK cells should also have a similar effect on tumors to upregulate PD-L1 expression on their surface.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Tregs developed from a miniscule subpopulation of donor T cells (<0.1% of total human lymphocytes) transferred with PM21-NK cells. Prior studies have shown that PD-L1 is critically required for the induction of Tregs from naïve CD4 T cells as well as their maintenance and immunosuppressive function 29 and the induction of its expression was thought to be caused mostly by CD8 T cells. 26 PD-L1 can also increase Treg content in PM21-NK cell product and decrease the NK/T cell ratio in vitro (Supplemental Figure 6).…”
Section: Discussionmentioning
confidence: 99%